Soil organic carbon forms with different uses in the department of magdalena (colombia) (2011)
Fractions of soil organic matter (SOM) labile and humified, can be affected by use and management practices, but the impact of these changes has not been evaluated in soils of tropical environments. The present study investigated the contents and some forms of soil organic carbon (SOC) in five warm tropical climate zones of the Department of Magdalena (Colombia), and the effect of the cropping practices on these forms of organic carbon in cultivated soils, associated with Coffee (Coffea arabica), Banana (Musa sp.), African palm (Elaeis guineensis), Aloe (Aloe vera) compared to natural forest soils. Significant differences (P and lt; 0.05) were not found between zones neither between soil. The study areas had low average values of SOM and, the forest soils had higher contents of total carbon than cultivated soils. Forest soils had an total carbon accumulation average of 42.4 mg/ha at 20 cm, compared to 33.8 mg/ha in the cultivated soils, this equals to an average loss of 23% total C by the effect of crop management in these soils. Values of humified C (C extracted with sodium pyrophosphate), are very low in cultivated soils and almost zero in forest soils, but forest soils had a higher number of stable forms of C (Cnox). In the soil cultivated with bananas, Total Carbon corresponds to fully oxidized forms of C, however in the soil cultivated with African palm, C stable forms represented 83% of total carbon.